Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Kosmetik Impor Tanpa Izin Edar Melalui Marketplace - Kharisma Putri, Varra; Budi Setianingrum, Reni (Adagium: Jurnal Ilmiah Hukum, 2025)
Imported cosmetic products circulated through marketplaces without a distribution permit from the Food and Drug Administration (BPOM) are illegal. This action is regulated by various regulations to enforce legal protection for consumers. Legal protection of consumers in the sale and purchase of imported cosmetics without a distribution permit is carried out by the Food and Drug Supervisory Agency (BPOM) which is authorized to supervise the circulation of imported cosmetic products in the marketplace by issuing a distribution permit certification for an imported cosmetic product that meets the standards and/or requirements by the provisions. The purpose of this study is to understand the legal protection of consumers in buying and selling imported cosmetics without a distribution permit from the Food and Drug Supervisory Agency (BPOM) online through the marketplace. This research uses a normative juridical research method with an approach to legislation. This research is descriptive in nature using literature studies which are then processed and analyzed using qualitative data analysis methods. The final result of this research is that consumers and business actors have rights and obligations to uphold legal protection for consumers. Legal protection of consumers in buying and selling imported cosmetics through the marketplace requires cooperation between the government, business actors and consumers.